A Life dedicated to the excellence research of fairy tales, picturebooks and childrens’ literature: Interview with Professor Bettina Kümmerling- Meibauer, from University of Tübingen - Garcia, André Luiz Ming (Literartes, 2020)
Bettina Kümmerling-Meibauer stands out today as one of the most important researchers of the themes listed in the title of this text, having a broad view and much experience about these fields of research. In this interview, we discuss with us current and even controversial themes involved in the fairy tale, offering us a privileged view of these issues arising from his notorious expertise. Following is the interview you kindly provided and, at the end, a summary of your academic curriculum and major publications. Good reading!